Unified handover authentication between heterogeneous access systems in LTE networks - Cao, Jin (2013)
To achieve seamless handovers between the Evolved Universal Terrestrial Radio Access Network (E-UTRAN) and other access networks is a challenging task as it requires comprehensive real-time interconnectivity in the LTE networks. The third Generation Partnership Project (3GPP) has suggested support the mobility between the E-UTRAN and non-3GPP access networks, which requires full access authentication procedures and distinct procedures for different mobility scenarios, which will bring a lot of message exchanges and increase the system complexity. Besides, the existing handover schemes for other wireless networks are not suitable for the mobility scenarios in the LTE networks due to their inherent vulnerabilities. In this paper, we propose a fast and secure handover authentication scheme to fit in with all of the mobility scenarios in the LTE networks. Compared with other handover schemes, our scheme cannot only provide strong security guarantees including Perfect Forward Secrecy (PFS) and Master Key Forward Secrecy (MKFS) and user anonymity, but also achieve a simple authentication process with robust efficiency in terms of communication cost, storage cost and computational cost. The analysis results show that the proposed scheme is efficient and secure against various malicious attacks.